Membrane distillation crystallization for water and mineral recovery: The occurrence of fouling and its control during wastewater treatment - Chimanlal, Indira; Nthunya, Lebea N.; Quist-Jensen, Cejna; Richards, Heidi (Frontiers in Chemical Engineering, 2022)
Membrane distillation crystallization (MDC) is an emerging technology envisaged to manage challenges affecting the desalination industry. This technology can sustainably treat concentrated solutions of produced water and industrially discharged saline wastewater. Simultaneous recovery of clean water and minerals is achieved through the integration of crystallization to membrane distillation (MD). MDC has received vast research interest because of its potential to treat hypersaline solutions. However, MDC still faces challenges in harnessing its industrial applications. Technically, MDC is affected by fouling/scaling and wetting thereby hindering practical application at the industrial level. This study reviews the occurrence of membrane fouling and wetting experienced with MDC. Additionally, existing developments carried out to address these challenges are critically reviewed. Finally, prospects suggesting the sustainability of this technology are highlighted.